2018
DOI: 10.1002/ecs2.2517
|View full text |Cite
|
Sign up to set email alerts
|

Mixed effects of urbanization on density, nest survival, and nestling corticosterone of a generalist passerine

Abstract: Generalist species occupy a wide range of habitats and typically respond well to environmental disturbance. Highly disturbed urban areas may contain habitat that generalists can use and exploit; however, habitat use and quality of areas within urban landscapes are poorly understood. Here, we investigated habitat use of a generalist passerine, the red‐winged blackbird (Agelaius phoeniceus), in urban and rural grassland patches in greater metropolitan Chicago, USA. From 2012 to 2013, we conducted point counts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…the response to a sudden, temporarily stressful event such as a predatory attack) between urban and non-urban populations (table 1). It is generally assumed that urban populations will show higher baseline levels of glucocorticoids due to chronic stress, but the results are mixed: while some studies find higher baseline glucocorticoid levels in urban populations [26,37], others find no effect [24,36] or even the opposite effect [30,45]. Similarly, the stress-induced responses of chronically stressed urban dwellers is generally expected to be higher than that of their non-urban counterparts, but, in this case too, the evidence is mixed [14,25,36].…”
Section: Introductionmentioning
confidence: 99%
“…the response to a sudden, temporarily stressful event such as a predatory attack) between urban and non-urban populations (table 1). It is generally assumed that urban populations will show higher baseline levels of glucocorticoids due to chronic stress, but the results are mixed: while some studies find higher baseline glucocorticoid levels in urban populations [26,37], others find no effect [24,36] or even the opposite effect [30,45]. Similarly, the stress-induced responses of chronically stressed urban dwellers is generally expected to be higher than that of their non-urban counterparts, but, in this case too, the evidence is mixed [14,25,36].…”
Section: Introductionmentioning
confidence: 99%
“…Those studies that did measure CORT in nestlings show mixed effects of urbanization. For instance, while pCORT did not vary between suburban and rural American crow nestlings ( Heiss et al 2009 ), rural red-winged blackbird nestlings had higher fecal CORT than urban ones ( Buxton et al 2018 ).…”
Section: Discussionmentioning
confidence: 93%
“…Although it is generally assumed that urban populations should have higher levels of cortisol metabolite due to chronic stress [8], previous studies showed diverse results, i.e. higher levels of cortisol metabolites [68,69], lower levels [39,70,71] or no differences [42,72]. Variations among studies might be related to complex responses of neuroendocrine system to chronic stress or species/population/individual-dependent differences in the perception of stressors [8].…”
Section: Stress Hormones In Hair and Fecesmentioning
confidence: 99%